A Biopolymer Coating Strategy for the Slow Release of Urea from Urea Fertiliser - Tuba Demirci; Tuğba Tecim Gelen; Nimet Bölgen (Kemija u Industriji, 2024)
Due to the rapid dissolution of urea fertilisers in water, leaching and evaporation from the soil cause approximately 70 % of the urea to be lost to the atmosphere and groundwater without being used by plants. It is known that a significant portion of urea fertiliser is released into the atmosphere as ammonia gas, and into groundwater as nitrate and nitrite, resulting in nitrogen losses. To mitigate these losses, various studies have been conducted on coating urea fertiliser with different materials. Biopolymers, in addition to providing controlled release, also act as soil conditioners by increasing the water-holding capacity of the soil and providing necessary moisture to plants during dry periods. In this study, three different types of biopolymers – chitosan, pectin, and xanthan gum – at two different concentrations (1 % and 3 %), were used to coat urea fertiliser aiming for controlled release. Biopolymer solutions and their cross-linkers were prepared, and the urea fertiliser was coated using a laboratory-scale coating drum. The chemical structure of the coated urea fertiliser was determined using Fourier-Transform Infrared Spectroscopy, and its morphology was examined with a Scanning Electron Microscope. The water-holding capacity in the soil and the ammonia released into the atmosphere were also analysed. The results indicated that the most effective biopolymer coating type for the slow-release mechanism of urea was pectin at a 1 % coating ratio on the fertiliser granules. The concentration of ammonia released from the soil and the water-holding capacity of the soil treated with biopolymer-coated urea fertiliser were tested through various experiments, and the results were analysed statistically. According to the statistical analysis, the 1 % pectin-coated urea fertiliser yielded the best results in both experiments, with an ammonia release value of 246.66 ppm and an evaporation rate of 67.84 % at the end of 30 days.